(untitled) (Third Sector Social Economic Review, 2024)
This study aims to determine the factors affecting students’ success in mathematics with PISA 2018 Data-Turkey covering 4473 students out of 6890. The factor analysis is applied to a wide range of 52 variables, including the number of weekly lessons in language, mathematics, and science courses to satisfaction with life, 14 factors are identified. After that, the multiple regression model is derived to find out the determinants of students’ success in mathematics. Besides these 14 factors, the gender of the students and the educational status of the parents are considered explanatory variables. Firstly, it is found that males and those whose fathers have higher levels of education have higher performance in mathematics. Among the factors, the wealth of family, use of information and communication technologies both outside and at the school, time spent to learn mathematics and science, perception of reading comprehension, and perception of cooperation at school are significantly positively associated with a student’s success. Furthermore, facing discrimination and bullying decreases student success in mathematics. The family’s socioeconomic status and access to information-communication technologies are the most important determinants of student success. Finally, it is recommended that reasonable support should be given to disadvantaged students for providing equal opportunity.